(untitled) (World Economics and Finance Bulletin, 2023)
To introduce the profitability index and the standard ratio determined by the Central Bank of Iraq based on and in line with the standard CAMELS, the role of this indicator and the extent of its contribution to the bank’s growth and capital increase, as well as evaluating the performance of banks with the profitability index and indicating its impact on achieving the requirements of banking governance.